Concomitant Trimodality Therapy of Re-irradiation, Chemotherapy and Regional Hyperthermia for a Pretreated Inoperable Sarcoma Recurrence. Issue 2 (March 2015) - Li, Minglun; Andrä, Claudia; Niyazi, Maximilian; Issels, Rolf D.; Abdel-Rahman, Sultan; Oskan, Feras; Manapov, Farkhad
We hereby present a case of pre-treated unresectable sarcoma recurrence of the trunk which showed an excellent response to concomitant tri-modal therapy, consisting of re-irradiation, chemotherapy and regional hyperthermia even with a strong compromised re-irradiation dose. No significant toxicity of the combined therapy and fast achievement of the pain and neurological symptoms relief are reported. The case shows that concurrent trimodality treatment can be considered as a therapeutic option for the management of pre-treated unresectable recurrence even in the re-irradiation setting.